2013
DOI: 10.3233/ies-130485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hamstring/quadriceps ratio between isoinertial and isokinetic measurements

Abstract: OBJECTIVE: To determine the applicability and predictive accuracy of an isoinertial resistance machine for the assessment of hamstring/quadriceps conventional (concentric) ratio (CR). METHOD: Thirty-two resistance trained young men (23.53 ± 3.2 yrs) were tested using dedicated instruments to obtain the peak torque (PT) of the right knee extensors and flexors as well as the corresponding one repetition maximum (1RM) values. All measurements were conducted in the concentric mode. RESULTS: Significant (p < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has also been indicated that knee isokinetic CR had a good correlation with isoinertial CR [24]. Da Silva et al [24] measured the relationship between both 1RM and PT, and CR and 1RM CR, and found that although the isoinertial method overestimated the isokinetic CR values, there was a significant and strong correlation between the two. These results indicate the possibility of using isoinertial machines to assess knee muscle balance by calculating 1RM CR.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has also been indicated that knee isokinetic CR had a good correlation with isoinertial CR [24]. Da Silva et al [24] measured the relationship between both 1RM and PT, and CR and 1RM CR, and found that although the isoinertial method overestimated the isokinetic CR values, there was a significant and strong correlation between the two. These results indicate the possibility of using isoinertial machines to assess knee muscle balance by calculating 1RM CR.…”
Section: Discussionmentioning
confidence: 97%
“…These results indicate the possibility of using isoinertial machines to assess knee muscle balance by calculating 1RM CR. Since isokinetic dynamometers are expensive assessment tools, 1RM CR could be tested via lower cost isoinertial equipment or free weights in order to monitor knee functionality [24]. Nevertheless, ECC testing is critical to muscle dynamics [15,25,26] and this assessment together with the actual DCR calculation should be encouraged if an active dynamometer is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation